(untitled) (UKLO Proceedings, 2026)
Introduction: This paper examines the relationship between two major ideological traditions in the European integration process—liberalism and European federalism—and explores the potential for their synthesis into a coherent political framework. Methods: The central research problem concerns the persistent heterogeneity of European Union (EU) member states with respect to their capacities and preferences for deeper integration, which continues to obstruct the realization of a free and united Europe. The study aims to investigate whether existing institutional mechanisms can facilitate the convergence of liberal and federalist ideas. The guiding research question is: Can liberalism and European federalism be combined into a viable political model for the EU through the mechanism of enhanced cooperation? Methodologically, the paper employs a theoretical analysis that integrates ideological inquiry with institutional examination. Attention is given to the provisions of the Lisbon Treaty, with a focus on enhanced cooperation as a pragmatic means of enabling differentiated integration. This framework is used to assess how diverse member states might simultaneously advance liberal and federalist objectives without requiring uniform participation. Results: The findings are presented in the conceptual model of Multi-Liberal Europe, a scenario in which member states apply liberal principles and federalist stages of integration in a differentiated manner. Discussion: This model provides a flexible, transitional mechanism for reconciling divergent national trajectories while maintaining broader momentum for integration. Although conceived as a provisional arrangement, the model aspires ultimately to contribute to the long-term vision of a Free and United Europe.